Sanções premiais de desenvolvimento multidimensional - Oliveira, Anderson Nogueira (2019)
The present study has the main objective to analyze the possible legal regulation of the awarding of sanctions that may be granted by public entities to the private initiative and to verify if such awarding sanctions meet the economic development model recognized by the country. Thus, this thesis has the following central problem: is there any legal regulation on premium sanctions that meets the economic development model intended by Brazil? To answer this question, the hypothetical-deductive method is adopted in this research, through bibliographic analysis, legislation and official data. As justification, it is highlighted the need to verify if the prize sanctions granted by public entities to the private initiative meet the precepts of economic development recognized by the country. It is noteworthy that the research has as theoretical reference: Hans Kelsen, in particular, regarding the classification of legal sanctions performed by him: coercive and premium, but here analyzed under the focus of economic induction to development desired by the state. For this, these study results are presented in three parts: first, through a historical analysis of the different conceptions of state interventions in the economy. Once the aforementioned historical bases are solidified, during the second part of this work, we proceed to an in-depth analysis of the premium sanction as a form of state intervention in the economy. Shortly afterwards, during the third part of the research, based on the classification created by the Mexican Julio Boltvinik, we verify the three possibilities of dimensions of economic development and its main indicators (one-dimensional, two-dimensional and multidimensional) in order to analyze which conception should to be adopted by Brazil and to verify if the award sanctions granted by public entities meet the development model recognized by the country. Therefore, this study has an innovative character, as it analyzes in depth if there is legal regulation on premium sanctions and whether these sanctions comply with the economic development model intended by Brazil. Finally, given the results of the research, a scientifically valid conclusion is reached